Teknik Guru Bertanya pada Pembelajaran Bahasa Indonesia Siswa Kelas 11 RPL 3 SMK Negeri Tugumulyo - Dian Ramadan Lazuardi; Ari Priyatno (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2017)
This Research aim to analyse skill enquire by Indonesian 11 RPL class student subject teacher 3 SMK Negeri Tugumulyo. Used by method research is descriptive method qualitative. this research location in SMK Negeri Tugumulyo Class 11 RPL. Data in this research that is result of record or record keeping.Source of especial data in this research is action and words. Technique analyse research data that is data transkripsi, data discount, displayed by data, verification, and conclude. Result of research indicate that skill enquire teacher at process study of Indonesian 11 RPL class student good SMK Negeri Tugumulyo. This matter seen from both aspect assessment of skill enquire, teacher fulfill all skill aspect enquire advanced and elementary storey level which amount to 60 question. Keyword: Enquiring, Base, and Continue